Improving The Quality Of Members Of The Mubaligat 'Aisyiyah (CMA) Corp In Malang District - Muhtadawati, Muhtadawati; Romelah, Romelah; Yazid, Syamsurizal (MUADDIB Jurnal Kependidikan dan Keislaman, 2023)
Efforts to improve the quality of CMA members in Malang district are important because the limited number of mubaligats available, the long distance between the coaching location and the mubaligat's domicile, multiple positions and jobs create time conflicts so they cannot be intensive in participating in coaching, and the use of social media is not optimal. as a medium for da'wah, therefore preacher training was held with the aim of producing qualified preacher cadres so that they are able to take part in the community of Malang district. The results are as follows: 1) Mubaligat training is important to carry out as a cadre of preachers and equalize perceptions of progressive Islamic ideology so that the Aisyiyah enlightenment preaching movement in the Malang district remains sustainable, 2) The implementation of mubaligat training has gone well according to plan, so there is an increase in understanding of the material for participants, as well as more confidence in preaching in society, and 3) Mubaligat training needs to be carried out periodically with continuous material in accordance with current developments